Efektivitas Modul Ipa Pbl-Steam Untuk Mengembangkan Keterampilan Proses Sains Siswa Dalam Pemecahan Masalah Pesawat Sederhana - Himatul Aliyah; Sulistyo Saputro; Sarwanto Sarwanto (Universitas Sebelas Maret, 2025)
This study tested the effectiveness of PBL-STEAM-based science modules (Problem-Based Learning - Science, Technology, Engineering, Arts, and Mathematics) in developing Science Process Skills (KPS) for students with simple airplane materials. Initial observations show the urgency of increasing student PPP in solving complex problems. This module is designed based on the PBL-STEAM syntax i.e. orientation; exploration and investigation; guided research; product creation, production, and presentation; product and process evaluation. The development research (R&D) using the Thiagarajan 4D model, involved grade VIII students of SMP Negeri 2 Balen, Bojonegoro, with one control class and two experimental classes. KPS data is collected through test instruments. Quantitative analysis includes prerequisite tests (normality, homogeneity) and independent sample t-test. The results of the Shapiro-Wilk normality test (p > 0.05) showed that all data were distributed normally. The results of the Levene's Test homogeneity test showed homogeneous pre-test data, with a significance value of 0.709 > 0.05. However, for post-test scores, the test results showed a significance of 0.000 < 0.05, indicating that the post-test data was not homogeneous, even though the independent sample t-test test could still be applied, The t-test results showed significant differences between the two groups, so that the IPA PBL-STEAM module proved to be effective and had a positive impact on improving students' KPS.